Orthopedic cast design and simulation: innovations for improved patient care - Winarso, Rochmad; Wibowo, Rianto; Hidayat, Taufiq; Laksono, Dwi Agung (Universitas Muria Kudus, 2024)
Some problems that often happen with clay casts are limited joint movement, muscle loss, and lower blood flow. There is a higher chance of systemic problems like clotting, local allergic reactions, skin trauma, compartment syndrome, and heat injuries. Plaster casts can cause skin sores from the pressure on the skin, skin infections, rashes, and stiffness in the joints over time. To get around these problems, many methods combining reverse engineering (RE) and additive manufacturing (AM) have been tested and shown to be effective in healing orthopedic casts problems, which are common fractures. Finite element analysis may be used to forecast the mechanical characteristics of devices such as orthopedic casts. In this study, we will use finite element analysis to examine the orthopedic cast designs' mechanical properties. Acrylonitrile butadiene styrene (ABS) was chosen as the material for this investigation because ABS is a recyclable material. A reduction in safety factor is observed as the weight imparted to the model increases. The utmost recommended burden at loading position 1 is 50 pounds of force. According to the findings derived from the simulations, the application of a 50-pound force burden will yield a safety factor of three. 10 pounds is the utmost weight that is recommended for loading position 2. This is based on the findings of the modeling, which suggest that the 10 lbf loading will generate a safety factor of 3.3. The maximum burden capacity that is advised for loading position 3 is 13 lbf. The deduction of this conclusion is supported by the simulation outcomes, which demonstrate that a 13-pound force application yields a safety factor of 3.01. 220 lbf is the utmost recommended force for loading position 4. Because the 220 lbf loading will produce a safety factor of 3.0, this is the case.